2009
DOI: 10.1080/10683160802409339
|View full text |Cite
|
Sign up to set email alerts
|

An interpersonal comparison of lone and group rape offences

Abstract: This study explores differences between group and lone sexual assaults, using a framework of interpersonal dimensions of dominanceÁsubmission and cooperationÁhostility (Alison & Stein, Journal of Forensic Psychiatry, 12, 515Á538, 2001). From archival sources, 120 cases (60 group and 60 lone offender assaults) were content analysed for offender, victim and context variables. A number of behavioural characteristics were found to differ between group and lone rape. Specifically, more hostile interactions were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 29 publications
8
73
1
2
Order By: Relevance
“…During the offense, use of violence appears to be somewhat more common in multiple-perpetrator sexual assaults than in lone-perpetrator sexual assaults (Morgan, Brittain, andWelch, 2012, andPorter andAlison, 2006). The results of research on use of weapons during multiple-perpetrator sexual assaults are mixed, however, such that some studies have shown greater use of weapons in multiple-perpetrator sexual assaults than in lone-perpetrator sexual assaults (Hauffe andPorter, 2009, andPorter andAlison, 2006) and others have not (Morgan, Brittain, and Welch, 2012). Completed vaginal rape is common in all multiple-perpetrator sexual assaults, and it is more common in multiple-perpetrator sexual assaults than in lone-perpetrator sexual assaults (Morgan, Brittain, andWelch, 2012, andUllman, 1999b).…”
Section: Descriptive Characteristics Of Multiple-perpetrator Sexual Amentioning
confidence: 99%
See 1 more Smart Citation
“…During the offense, use of violence appears to be somewhat more common in multiple-perpetrator sexual assaults than in lone-perpetrator sexual assaults (Morgan, Brittain, andWelch, 2012, andPorter andAlison, 2006). The results of research on use of weapons during multiple-perpetrator sexual assaults are mixed, however, such that some studies have shown greater use of weapons in multiple-perpetrator sexual assaults than in lone-perpetrator sexual assaults (Hauffe andPorter, 2009, andPorter andAlison, 2006) and others have not (Morgan, Brittain, and Welch, 2012). Completed vaginal rape is common in all multiple-perpetrator sexual assaults, and it is more common in multiple-perpetrator sexual assaults than in lone-perpetrator sexual assaults (Morgan, Brittain, andWelch, 2012, andUllman, 1999b).…”
Section: Descriptive Characteristics Of Multiple-perpetrator Sexual Amentioning
confidence: 99%
“…On average, multipleperpetrator sexual assault offenders are younger than lone offenders. Their average age tends to be approximately 21 to 22 years (Hauffe andPorter, 2009, andUllman, 1999b), and they tend to choose victims who are approximately their same age or slightly younger (Porter and Alison, 2006). In addition, multiple-perpetrator sexual assault offenders are significantly more likely than lone-perpetrator sexual assault offenders to have a history of drug or alcohol abuse (Hauffe and Porter, 2009).…”
Section: Characteristics Of Multiple-perpetrator Sexual Assault Offenmentioning
confidence: 99%
“…Hickle and RoeSepowitz (2010) found lone juvenile arsonists more often came from unstable homes, and experienced school difficulties, behavioral problems, negative emotions, and expressed suicidal thoughts more regularly. Hauffe and Porter (2009) suggest differing pathological processes at play between lone and group offenders.…”
Section: Mental Illness and Selection Effectsmentioning
confidence: 99%
“…This is an important gap as we know from previous research that there may be important differences between (adult) sexual offenders who act alone and sexual offenders who operate with co-offenders (Bijleveld & Hendriks, 2003;Hauffe & Porter, 2009;Wright & West, 1981) In fact, adult female sexual offenders very often co-offend. The co-offenders is usually a man, who is often their intimate partner.…”
Section: Introductionmentioning
confidence: 97%
“…Not much is known about the personality characteristics of juvenile male group sexual assault offenders, and some researchers reported that their personality Group sexual offending by juvenile females 6 profiles appear average and not different from other, non-sexual offenders (De Wree, 2004, Woods, 1969, Wright & West, 1981. Sexual abuse victimization of offenders themselves is reported to be low (between six and eight per cent) (Bijleveld & Hendriks, 2003, Hauffe & Porter, 2009). Psychiatric problems were seldom reported: 4% (Porter & Alison, 2006) to 7% (Bijleveld & Hendriks, 2003) .…”
Section: Previous Research On Male Juvenile Group Sexual Offendersmentioning
confidence: 99%